Genetic aspects of endothelium dysfunction in Uzbek hypertensive patients - Khamidullaeva, Gulnoza; Kevorkov, Amayak; Eliseyeva, Marietta (Medical and Health Science Journal, 2010)
The objective of the study was to evaluate the prevalence of ACE/ID, AGT/M235T, AT1R/A1166C, CYP11B2/C344T, B2ВKR/ 9-9, ecNOS/4a4b, GNB3/C825T, and ARB2/Gln27Glu gene polymorphisms and their association with endothelium dysfunction (ED) in Uzbek hypertensive patients. The study found an association between ED and AGT M235T gene polymorphism. Genetic models disclosed that the T-allele, MT-, and TT-genotypes of the AGT gene were associated with an increased risk of ED. However, multivariate logistic regression analysis confirmed the negative association between the MM genotype of the AGT gene and positive association between IMT and ED. An association between essential hypertension (EH) in Uzbek males with ACE/ID and GNB3/C825T gene polymorphisms has been demonstrated. There is an
Keywords: bradykinin B2-receptor; dospělí; Amplified Fragment Length Polymorphism Analysis; beta2-adrenoreceptor; hypertenze; Genotype; angiotensin konvertující enzym; Endothelium, Vascular; multivariační analýza; Receptor, Angiotensin, Type 1; Adult; angiotensinogen; receptor angiotensinu typ 1; Multivariate Analysis; cytochrom P450 CYP11B2; analýza polymorfismu délky amplifikovaných restrikčních fragmentů; lidé; genotyp; Cytochrome P-450 CYP11B2; Peptidyl-Dipeptidase A; synthasa oxidu dusnatého, typ III; Uzbekistán; Hypertension; Male; polymorfismus genetický; alely; cévní endotel; Alleles; Nitric Oxide Synthase Type III; lidé středního věku; mužské pohlaví; Angiotensinogen; Uzbekistan; Polymorphism, Genetic; heterotrimerní G-proteiny; Middle Aged; Heterotrimeric GTP-Binding Proteins; Humans